2000
DOI: 10.1016/s1573-5214(00)80008-1
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the economic values of novel cropping systems in N. E. Thailand and S. Sumatra

Abstract: The use of food-crop intercropping, hedgerow intercropping and secondary or cover cropping to increase incomes of resource-poor farmers in South East Asia was investigated. Since all systems improve conservation of nutrients and most give extra marketable produce, they were expected to increase farm profitability. On upland farms in Lampung, South Sumatra, both inter-and secondary crops were found to improve yields compared with cassava monocropping and thus the income derived from growing cassava or rice with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…It is now well recognized that green manure legumes can greatly increase nitrogen supply to the soil, improve soil chemical, physical and biological properties but they are often poorly adopted by farmers (Whitmore et al, 2000). Greater emphasis is thus placed on the use and management of grain legumes which directly improve farmers' income while also benefiting soil fertility.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well recognized that green manure legumes can greatly increase nitrogen supply to the soil, improve soil chemical, physical and biological properties but they are often poorly adopted by farmers (Whitmore et al, 2000). Greater emphasis is thus placed on the use and management of grain legumes which directly improve farmers' income while also benefiting soil fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming 300 work days per year for 50% of the total population and 80% of the land area available for productive land use level. Whitmore et al (2000) concluded that improved soil management practices in intensive intercropping practices following forest conversion with groundnut or cowpea can substantially increase income above the current farm practice, but in the surrounding landscape most of the soils may have been degraded too far for this option to still be available. Gradual conversion of the cassava fi elds (alternating with Imperata cylindrica dominated fallows) to tree-based production systems may provide better options.…”
Section: Way Kanan Asb Benchmarkmentioning
confidence: 99%
“…The use of poultry manure as it affects NERICA 1 improves its grain yield (2.78 tha -1 , grains per panicle (191), panicle weight (32g), panicle length (27cm), culm weight (172g) and number of tillers (18) per hill (Oyekanmi et al, 2009). The adoption of legumes into rice-based cropping systems offers opportunities to increase and sustain productivity and income of smallholder farmers (Whitmore et al, 2000 andWijnhoud et al, 2003). Incorporation of organic materials in the form of crop residues enhances the organic carbon level of the soil (Sarkar et.…”
Section: Introductionmentioning
confidence: 99%